CMOS-compatible Eu2+-doped CsCu2I3 films with improved quantum yield for white-light emission and information encryption - Daoping Peng; Lichun Zhang; Xiaoxuan Li; Xiao Zhang; Yu Fang; Chenxi Han; Ziyan Wan; Xiaohua Cheng; Guanying Xie; Zhongqiang Wang; Congcong Liu; Mengmeng Jiao; et al. (Chemical Engineering Journal, 2026)

Spatiotemporal Patterns of Echolocation Activity of the Yangtze Finless Porpoises ( Neophocaena asiaeorientalis ) Near Mid‐Channel Islands in the Yangtze River - Daoping Yu; Kangwei Wang; Minmin Chen; Yuxi Lian; Longfei Huang (Marine Mammal Science, 2026)
Understanding fine‐scale habitat use is essential for conservation of endangered freshwater cetaceans in large rivers. Although Yangtze finless porpoises ( Neophocaena asiaeorientalis ) are frequently observed near mid‐channel islands, their spatiotemporal use of different island geomorphic units remains poorly resolved. From January 2021 to July 2022, passive acoustic monitoring was used to investigate echolocation activity of porpoises at three geomorphic units (head, middle, and tail) of Qingjiezhou Island in an anabranching reach of the Yangtze River. Porpoise acoustic activity exhibited significant seasonal and spatial variation. During the wet season, both daily detection rate (DDR) and sequent log window (SLW) were highest at the island middle and tail, whereas activity during the dry season was greatest at the island head, likely influenced by fish aggregation associated with sluice gate operation. Spatial heterogeneity in echolocation activity among geomorphic units was significant during the wet season but less pronounced during the dry season. A strong positive correlation was observed between DDR and mean daily SLW, indicating consistent patterns of habitat use intensity. Our findings demonstrate that mid‐channel islands function as seasonal mini‐floodplains and critical habitats for Yangtze finless porpoises, underscoring the importance of incorporating island geomorphic units into conservation planning for large river ecosystems.

Rapid methane hydrate formation in micro droplets of graphite nanoparticles suspension - Yu Xie; Xin Lan; Ni Liu; Yingming Xie; Zheyuan Liu; Daoping Liu; Liang Yang (Fuel, 2026)

Non-monotonic effects of soil particle size on UV-assisted electrokinetic remediation of Cr(VI) contaminated soils - Yi Zheng; Yingjun Xie; Zao Jiang; Liang Zhang; Huilin Li; Qiu Yu; Daoping Peng; Yibo Zhang (Journal of Soils and Sediments, 2025)

Designing a size exclusion-based hapten and the development of a quantitative and visual time-resolved fluorescence immunochromatography assay strip for detecting dimethomorph and flumorph in a group-specific manner - Yuxian Zhu; Yongyi Zhang; Daoping Zeng; Haoyu Chen; Yu Wang; Jinyi Yang; Hong Wang; Zhenlin Xu; Yuanming Sun; Yuanxin Tian; Yudong Shen (Food Chemistry, 2024)

Hydraulic conductivity and multi-scale pore structure of polymer-enhanced geosynthetic clay liners permeated with bauxite liquors - Xing Chen; Yu Tan; Jiannan Chen; Daoping Peng; Tao Huang; Chunxiao Meng (Geotextiles and Geomembranes, 2024)

Corrigendum to ‘Vorticity preference of the Yangtze finless porpoise (Neophocaena asiaeorientalis) during the dry season at the Wanhe River Estuary confluence’ - Rui Ding; Xiaoke Zhang; Minmin Chen; Yuxi Lian; Daoping Yu (Ecological Modelling, 2023)

Applications of advanced materials in the pretreatment and rapid detection of small molecules in foods: A review - Zhizhou Ling; Jinyi Yang; Yongyi Zhang; Daoping Zeng; Yu Wang; Yuanxin Tian; Hong Wang; Zhenlin Xu; Yuanming Sun; Yudong Shen (Trends in Food Science & Technology, 2023)

Vorticity preference of the Yangtze finless porpoise (Neophocaena asiaeorientalis) during the dry season at the Wanhe River Estuary confluence - Rui Ding; Xiaoke Zhang; Minmin Chen; Yuxi Lian; Daoping Yu (Ecological Modelling, 2023)

Polymer elution and hydraulic conductivity of polymer-bentonite geosynthetic clay liners to bauxite liquors - Xing Chen; Yu Tan; Tim Copeland; Jiannan Chen; Daoping Peng; Tao Huang (Applied Clay Science, 2023)

Pricing-decision analysis of green supply chain with two competitive manufacturers considering horizontal and vertical fairness concerns - Daoping Wang; Genhasi Ge; Yu Zhou; Mengying Zhu (Environmental Science and Pollution Research, 2022)

An efficient micropropagation protocol, chemical components, and hypoglycemic activity for Cremastra appendiculata (D. Don) Makino pseudobulbs - Ningxian Yang; Daoping Wang; Yanyan Gao; Enming Hu; Xiaosong Yu; Sijing Peng; Jun Ji; Ming-sheng Zhang (In Vitro Cellular & Developmental Biology - Plant, 2022)

Characterization of milk protein composition of the Yangtze finless porpoise - Xianyuan Zeng; Minmin Chen; Zhigang Liu; Daoping Yu; Shiang‐Lin Huang; Jiwei Yang; Fei Fan; Ding Wang; Yujiang Hao; Ghulam Nabi (Marine Mammal Science, 2019)

Effects of fish community on occurrences of Yangtze finless porpoise in confluence of the Yangtze and Wanhe Rivers - Xiaoke Zhang; Daoping Yu; Huili Wang; An Wan; Minmin Chen; Feng Tao; Zunrong Song (Environmental Science and Pollution Research, 2015)